ANALISIS KETIDAKSIAPAN BELAJAR PESERTA DIDIK DALAM MENGIKUTI PEMBELAJARAN DARING KELAS VIII DI SMP NEGERI 23 PONTIANAK - Lai Suni; Indri Astuti; Ana Fergina (Universitas Tanjungpura, 2022)
This study aims to analyze the unreadiness of students in online learning in grade VIII of State Senior High School (SMP) number 23 Pontianak. The research method used in this study was descriptive in the form of a survey study. The data was collected through a questionnaire. Sixty students participated in this research finding showed that more than 70% of students were not ready to study online. The research analyzed eight aspects of unreadiness in learning online. The physical and mental elements showed 78%. The skill and goal aspects shared the same score 78%. The lowest score was in motivation at 65%, and the highest was in knowledge at 81%. It can be concluded that the category of unreadiness of students in online learning was high at 74%, and they were not ready to study online. The various causes made this happen. Further research may be conducted to see strategies for how to teach prepare students to learn online.